Drgawki noworodkowe przyczyną właściwej diagnozy u matki - Gupta, Saniya; Yadav, Jaivinder; Kumar, Rakesh; Saini, Lokesh; Vankadari, Kousik; Dayal, Devi (Pediatric Endocrinology Diabetes and Metabolism, 2021)
Fetus and neonate are dependent maternal supply of calcium for maintaining the calcium profile in physiologic range. The disturbances in maternal calcium homeostasis leads to changes in the baby’s calcium. Maternal investigations in neonatal hypocalcemia not only reveal the etiology in the baby but are sometime helpful in unmasking maternal disorder of calcium homeostasis.